Serum Vitamin D Levels in Different Phenotypes of Polycystic Ovarian Syndrome (PCOS) A Case-Control Study: Life Sciences-Medicine - MD, Seetesh Ghose; Manasa, Karri Lakshmi; Ravirajan, Mangaiyarkarasi (International Journal of Life Science and Pharma Research, 2022)
Polycystic ovarian syndrome (PCOS) is the most common heterogeneous multisystem endocrinopathy in women of reproductive age, with an ovarian manifestation of various metabolic disturbances. Based on Rotterdam criteria, PCOS is further classified into four phenotypes. Vitamin D deficiency affects 65- 75% of PCOS patients. There is very little research on the relationship between vitamin D deficiency and PCOS phenotypes. As a result, we intended to investigate the relationship between vitamin D, PCOS, and various PCOS phenotypes. This is a case-control study where we had been 100 people in the study. A total of 50 PCOS participants were classified into phenotype A, phenotype B, phenotype C, and phenotype D using Rotterdam criteria. There were 50 participants who did not have PCOS. Serum vitamin D levels were measured in the study population. The CIDRF (Central Inter-Disciplinary Research Facility) used an ELISA kit and reader to quantify vitamins. The results obtained were further classified as deficient (20ng/ml), insufficient (21-29ng/ml), and sufficient (30ng/ml). SPSS version 17 was used to analyse the results. The mean vitamin D level among women with PCOS was 15.9±9.3, women without PCOS was 20.5±9.2, the difference between the means was statistically significant(p-0.015). Among the participants with PCOS Phenotype A accounted for 36%, phenotype B 26%, phenotype C 20%, phenotype D 18%. The serum vitamin D levels among different phenotypes of PCOS was not statistically significant (p-0.978). There was no statistically significant difference in the mean vitamin D levels, among the phenotypes of PCOS (p - 0.978). Vitamin D deficiency was found to be more prevalent in women with PCOS in this study. In PCOS, it is recommended to screen for and treat with vitamin D. There is no significant difference between phenotypes.